Three new species of Lepanthes (Pleurothalldinae: Orchidaceae) From Amazonas, Peru - Damian, A (2017)
Three new species of Lepanthes (Orchidaceae: Pleurothallidinae) from Northern Peru are described here. Each species is illustrated with a line drawing, also a photograph for each one is presented. For each species information about distribution, habitat, and a comparison with similar taxa is given. The new species are named as Lepanthes pseudoprofusa, Lepanthes odobenus, and Lepanthes peruviana.